A Study of Composite Salt Erosion Resistance of Nano-Modified Cement Mortar in Early Ages - Jia Guo; Tao Zheng; Fei Mou; Yang Qin; Zhi Wang; Shiyi Zhang; Hui Li (Buildings)
Corrosion of traditional cement mortar is a critical issue in karst areas. Composite salt, i.e., sulfate–chloride salt, represents a typical corrosion agent due to the abundance of Cl− and SO42− ions in such geological environments. In this study, we used nano-metakaolin to enhance the physical and mechanical properties of cement mortar in the early aging stages, simulating groundwater corrosion by a compound salt solution in the karst region. The appearance and the change in the flexural/compressive strength of cement mortar upon the nano-metakaolin addition in the early aging stages under dry and wet cycling conditions were analyzed and combined with the results of scanning electron microscopy, thermogravimetric analysis, and other methods, revealing the underpinning mechanism behind the function changes of nano-metakaolin-modified cement mortar. The results show that nano-metakaolin effectively promotes cement hydration in the early aging stages. The flexural/compressive strength after 7 days of aging with 1% of added nano-metakaolin increased by 10.38% and 4.41%, respectively, compared to ordinary cement mortar. Furthermore, adding 1–5% of nano-metakaolin under dry and wet cycling and the coupling effect of chloride and sulfate erosion effectively reduce the damage of harmful ions on the cement mortar, leading to evident corrosion inhibition. The generation of hydration products increased after adding the Ghanaian metakaolin, filling the microcracks and micropores, and increasing the overall microstructural compactness.